PENCEGAHAN STUNTING MELALUI PEMBERDAYAAN KADER PKK KECAMATAN BAREBBO DI KABUPATEN BONE - Citra Kesumasari; Yessy Kurniati; Aminuddin Syam; Abdul Salam; Devintha Virani (LP2M Universitas Hasanuddin, 2020)
Prevention of Stunting Through Empowerment of Family Welfare Programme Cadres in Barebbo District in Bone RegencyAbstract. Bone Regency has the highest prevalence of stunting under five in South Sulawesi, after Enrekang district. Family Welfare Programme (PKK) cadres are often empowered in overcoming various problems in the community. This dedication activity aims to empower PKK cadres to prevent stunting in the Barebbo District, Bone Regency. Audience The target of this training is PKK cadres in Barebb Subdistrict. The Community Service Method is to provide training to PKK cadres on stunting prevention. The training was carried out in two ways, namely by providing material on stunting and demonstrations on how to screen stunting to children through anthropometric measurements. Based on the results of the activities carried out, it appears that the training carried out has increased the knowledge of PKK cadres who were trained in the good category by 54.5%. This is in accordance with established indicators of success. The training carried out effectively increased the knowledge and skills of PKK cadres in conducting anthropometric measurements. This is important in preventing stunting in infants. PKK cadres who have been trained are expected to be able to contribute significantly in screening the status of toddlers in the community.Keywords: Toddlers, stunting, prevention, anthropometry. Abstrak. Kabupaten Bone menjadi kabupaten yang memiliki prevalensi balita stunting tertinggi di Sulawesi Selatan, setelah kabupaten Enrekang. Kader PKK sering diberdayakan dalam mengatasi berbagai masalah dalam masyarakat. kegiatan pengabdian ini bertujuan untuk memberdayakan kader PKK untuk mencegah terjadinya stunting di Kecamatan Barebbo, Kabupaten Bone. Khalayak Sasaran pada pelatihan ini adalah kader PKK di Kecamatan Barebbo.Metode Pengabdian yang dilakukan adalah dengan memberikan pelatihan kepada kader PKK tentang pencegahan stunting. Pelatihan tersebut dilakukan dengan dua cara, yaitu dengan pemberian materi tentang stunting dan demonstrasi tentang cara melakukan skreening stunting pada balita melalui pengukuran antropometri. Berdasarkan hasil kegiatan yang telah dilakukan, terlihat bahwa pelatihan yang dilakukan telah meningkatkan pengetahuan kader PKK yang dilatih pada kategori baik sebesar 54,5%. Hal ini telah sesuai dengan indikator keberhasilan yang telah ditetapkan. Pelatihan yang dilakukan efektif meningkatkan pengetahuan dan keterampilan kader PKK dalam melakukan pengukuran antropometri. Hal tersebut penting dalam melakukan pencegahan stunting pada balita. Kader PKK yang telah dilatih diharapkan mampu berkontribusi secara nyata dalam melakukan skreening status balita di masyarakat.Kata Kunci : Balita, stunting, pencegahan, antropometri